2008
DOI: 10.1007/s10803-008-0612-4
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Relationship Between Non-verbal IQ and Gender in Autism

Abstract: It has been proposed that females at risk for autism are protected in some way, so that only those with the greatest genetic liability are affected. Consequently, affected male siblings of females with autism should be more impaired than affected male siblings of male probands. One hundred and ninety-four (194) families with a single child with autism (simplex, SPX) and 154 families with more than one child with autism (multiplex, MPX) were examined on measures of severity, including non-verbal IQ. Among SPX f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 23 publications
8
64
4
Order By: Relevance
“…Therefore, we could not detect the gender differences on RRB in our sample. However, in line with the results of other reports, we found no differences in severity of autism symptoms between males and females either across time or at a specific time assessment (nor at T0 or at T1; Carter et al 2007;Banach et al 2009;Andersson et al 2013;Mayes and Calhoun 2011;Zwaigenbaum et al 2012;Mandy et al 2012;Szatmari et al 2012;Donna et al 2013). Furthermore, our results have shown no significant interaction between time and gender for predicting cognitive ability, parental stress, children's adaptive skills or behavior problems.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, we could not detect the gender differences on RRB in our sample. However, in line with the results of other reports, we found no differences in severity of autism symptoms between males and females either across time or at a specific time assessment (nor at T0 or at T1; Carter et al 2007;Banach et al 2009;Andersson et al 2013;Mayes and Calhoun 2011;Zwaigenbaum et al 2012;Mandy et al 2012;Szatmari et al 2012;Donna et al 2013). Furthermore, our results have shown no significant interaction between time and gender for predicting cognitive ability, parental stress, children's adaptive skills or behavior problems.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the available findings on the differences in clinical profiles between males and females with ASD have J Autism Dev Disord (2015) 45:2046-2055 2049 Table 1 ADOS severity score, GMDS-ER and VABS-SF at T0 and T1 Autism Dev Disord (2015) 45:2046-20552051 shown contrasting results (Carter et al 2007;Banach et al 2009;Andersson et al 2013;Van Wijngaarden-Cremers et al 2013;Hofvander et al 2009;Lugnegard et al 2011;Matson and Nebel-Schwalm 2007;Park et al 2012;Simonoff et al 2008;Lai et al 2011;Mayes and Calhoun 2011;Zwaigenbaum et al 2012;Mandy et al 2012;Szatmari et al 2012;Donna et al 2013). On the one hand, most studies found no gender differences on social behaviors or communication nor on RRB (Carter et al 2007;Banach et al 2009;Andersson et al 2013;Hofvander et al 2009;Lugnegard et al 2011;Matson and Nebel-Schwalm 2007;Park et al 2012;Simonoff et al 2008;Lai et al 2011;Mayes and Calhoun 2011;Zwaigenbaum et al 2012;Mandy et al 2012). For instance, Andersson et al (2013), in a cross-sectional study aimed at investigating gender differences in clinical and developmental profiles in 20 preschool girls and 20 age-matched preschool boys with suspected ASD, found no significant differences on communication and RRB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No sex differences existed on measures of social reciprocity in our analyses suggesting that the mechanism underlying sex differences in ASD is either restricted to the BEH domain or else there are measurement effects or other covariates that influence social reciprocity and so the familial effect is obscured. The results in this paper are also somewhat different than our earlier paper on sex differences in IQ which showed (in a sub-sample of the AGP from the Canadian site that was part of this study) that in families with a single affected individual, females are more severely affected than boys, whereas no such differences exist in multiple incidence families [Banach et al, 2009]. Putting these findings together adds to the growing evidence of the fractionation of the ASD phenotype into social-communication, and BEH [Happe and Ronald, 2008;Mandy and Skuse, 2008] and possibly IQ [Banach et al, 2009] with possibly different genotype-phenotype relationships.…”
contrasting
confidence: 99%
“…The ratio is apparently greater than 4:1 among children with IQ's above 70 [Lord and Schopler, 1985;Volkmar et al, 1993;McLennan et al, 1993]. This, however, only appears to be true in families with a single affected child; in multiple incidence families the 4 to 1 sex ratio is constant across IQ strata [Banach et al, 2009]. It is also important to note that studies Additional supporting information may be found in the online version of this article.…”
mentioning
confidence: 99%